Development and performance of iron based oxygen carriers containing calcium ferrites for chemical looping combustion and production of hydrogen. (23rd February 2016) - Ismail, Mohammad; Liu, Wen; Dunstan, Matthew T.; Scott, Stuart A.
Abstract: Chemical looping combustion (CLC) is a cyclic process in which an oxygen carrier (OC), is firstly reduced by a fuel, e.g . syngas, and then oxidised in air to produce heat. If the OC is Fe2 O3, the oxidation can take place in steam to produce hydrogen, i.e. chemical looping hydrogen production (CLH). This paper presents an investigation of CaO modified Fe2 O3 OCs for CLC and CLH. The performance of the mechanically mixed OCs were examined in a thermogravimetric analyser and a fluidised bed. It was found that the addition of CaO gives cyclic stability and additional capacity to produce hydrogen via CLH, at the expense of reduced oxygen carrying capacity for CLC, owing to the formation of calcium ferrites, such as Ca2 Fe2 O5 . Highlights: CaO-modified iron oxide oxygen carriers containing mono and di-calcium ferrite have been synthesised. The CaO-modified oxygen carriers gave more stable performance over chemical looping cycles than unmodified Fe2 O3 . The Fe in the calcium ferrites fully participated in the redox cycles, but the proportions of the ferrites changed. The Fe in the di-calcium ferrite is unavailable for CLC but can be fully utilised for H2 production.